The Analysis of Milkfish (Chanos chanos) Business in Fishbond At Sungai Undan Village Reteh Subdistrict Indragiri Hilir District of Riau Province - Imawan, Riswanda; ', Hendrik; ', Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The purposes of this research to find out the cost of investment, to know the feasibility business and the problems and prospects in milkfish fishpond with in size of 1,5 Ha, 2,0 Ha and 4,0 Ha in Sungai Undan Village Reteh Subdistrict Indragiri Hilir District of Riau Province. Based on the results of the reseach, the average cost of investment to fishpond size 1,5 is Rp 42.082.400,00- with benefit Rp 8.836.250,00-/period(5-6 month), fishpond size 2,0 Ha is Rp 51.932.500,00- with benefit Rp 14.068.750,00-/period(5-6 month) and fishpond size 4,0 Ha is Rp 103.467.500,00- with benefit Rp 16.760.000,00-/period(5-6 month). Based on faseability criteria, it can be said that milkfish fishpond is worth to be developed but there are some problems faced by farmers such as the availability of ready stock nener or gelondongan (2-4 cm), the long distance for purchasing nener in Bali, public facilities that are inadequate, there are no field facilitator, and the habit of farmer to flipping commodity fishpond. Fishpond of milkfish has good prospect to be developed by the support of some aspect in this area.Keywords: Milkfish, Production, Business Analytics